Relatively high levels of serum adiponectin in obese women, a potential indicator of anti-inflammatory dysfunction: Relation to sex hormone-binding globulin - Onat, Altan; Hergenc, Guelay; Dursunoglu, Dursun; Kucukdurmaz, Zekeriya; Bulur, Serkan; Can, Guenay (IVYSPRING INT PUBL, 2008)
It is unclear whether serum adiponectin concentrations diminish linearly with increasing adiposity and, if not, which factors codetermine this association. These issues were investigated cross-sectionally in 1188 men and women, representative of middle-aged and elderly Turkish adults. Serum total adiponectin was assayed by ELISA. Serum adiponectin values in men, though declining significantly in transition from the bottom to the mid tertile of body mass index (BMI) and waist circumference (WC), were similar in the two respective upper tertiles. In women, serum adiponectin concentrations were not significantly different in any tertile of these indices, were significantly correlated with BMI or WC within the low tertiles and not within the two higher tertiles. In a linear regression analysis for WC (or BMI) in a subset of the sample in which serum sex hormone-binding globulin (SHBG) was available and which additionally comprised adiponectin, fasting insulin and other confounders, only insulin and, in women SHBG, were significantly associated, but not adiponectin. In linear regression analyses for covariates of adiponectin in two models comprising 12 variables, insulin and SHBG concentrations were significantly associated in both genders though not BMI. Whereas in men HDL-cholesterol and CRP were covariates of adiponectin (both p<0.01), SHBG and apolipoprotein B positively associated in women (p<0.001), independent of BMI and fasting insulin levels. Conclusions: Relationship between excess adiposity and adiponectin levels is inconsistent in Turkish adults. Independently from obesity and hyperinsulinemia, serum adiponectin discloses significant relationship with inflammatory markers and HDL only in men, not in women in whom it is influenced by SHBG, with consequent attenuation of its anti-inflammatory activities.
Keywords: Adiponectin; anti-inflammatory function; gender difference; waist circumference; obesity; sex hormone-binding globulin; CORONARY-HEART-DISEASE; PLASMA ADIPONECTIN; INSULIN-RESISTANCE; METABOLIC SYNDROME; ABDOMINAL OBESITY; RISK; MEN; DYSLIPIDEMIA; POPULATION; MORTALITY; Biochemistry & Molecular Biology; Life Sciences & Biomedicine - Other Topics